The correlation analysis of unemployment, corruption and population toward poverty in developing countries (Asia) - Noikin, Audrey Isabella (2014)
There are many people die every day because of hunger or any hunger-related causes. According to the United Nations, there are about 25,000 people die because of this causes. This is approximately seventeen people every minute. Statistically, it is the children who die most often. Poverty reduction became ultimate goal and issue for many international organizations such as the World Bank and the United Nations since their formation. The World Bank's mission has been carved in stone at Washington headquarters stated "Their dream is a world free of poverty." The purpose of this paper is to explore search more about the causes of poverty with doing a correlation test of the relationship between unemployment, corruption, and population towards the level of poverty.